2009
DOI: 10.3155/1047-3289.59.7.865
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Characterizing Fine Particulate Matter Using Ground Observations and Remotely Sensed Data: Potential Use for Environmental Public Health Surveillance

Abstract: This study describes and demonstrates different techniques for surface fitting daily environmental hazards data of particulate matter with aerodynamic diameter less than or equal to 2.5 m (PM 2.5 ) for the purpose of integrating respiratory health and environmental data for the Centers for Disease Control and Prevention (CDC) pilot study of Health and Environment Linked for Information Exchange (HELIX)-Atlanta. It presents a methodology for estimating daily spatial surfaces of ground-level PM 2.5 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 25 publications
0
56
0
Order By: Relevance
“…This is helpful for tracking pollution levels for use in assuring compliance with national standards, but it does not allow us to gain an accurate regional perspective on PM 2.5 . Studies in recent years [27][28][29][30] have shown that a combination of ground PM 2.5 measurements and satellite retrieved AOT can provide a better spatial assessment than ground observations alone at regional to global scales.…”
Section: Results and Observationsmentioning
confidence: 99%
“…This is helpful for tracking pollution levels for use in assuring compliance with national standards, but it does not allow us to gain an accurate regional perspective on PM 2.5 . Studies in recent years [27][28][29][30] have shown that a combination of ground PM 2.5 measurements and satellite retrieved AOT can provide a better spatial assessment than ground observations alone at regional to global scales.…”
Section: Results and Observationsmentioning
confidence: 99%
“…(1) Model predictability: MLR was commonly used in early studies [17,20,21,[24][25][26][39][40][41]46,47,49,50,54,75], whereas MEM and CTM gradually became the dominant methods and replaced MLR after 2010. However, GWR has developed at a slower pace with a limited number of studies to data, and had moderate performance [32,74,125,126].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in order to improve model performance, some studies have explored covariate factors in the MLR model under different conditions [17,20,21,[24][25][26][39][40][41]46,47,49,50,54,75]. A few covariate factors, such as relative humidity and height of the boundary layer, were regarded as significant enough to affect and even invert the relationships between AOD and PM 2.5 .…”
Section: Theory Background and Applicationmentioning
confidence: 99%
“…The need for greater collaboration of air quality and space scientists is evident in an article published in the July issue of the journal. 57 AlHamdan et al 57 provide an interesting and useful analysis of relationships between surface air quality and spacebased satellite AOD to estimate human exposure. They obtain mostly urban PM data from EPA's Air Quality System (AQS), 58,59 but they neglect the potentially more useful PM 2.5 and chemical speciation data from the nonurban Interagency Monitoring of Protected Visual Environments (IMPROVE) 47,60 and the Southeastern Aerosol Research and Characterization (SEARCH) [61][62][63] networks.…”
Section: Discussionmentioning
confidence: 99%